PADI6 Regulates Trophoblast Cell Migration-Invasion Through the Hippo/YAP1 Pathway in Hydatidiform Moles - Huang B; Zhao Y; Zhou L; Gong T; Feng J; Han P; Qian J (Dove Medical Press, 2021)
Bo Huang,* Yating Zhao,* Lin Zhou,* Tingyu Gong, Jiawen Feng, Peilin Han, Jianhua Qian Department of Gynecology and Obstetrics, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou City, 310003, Zhejiang Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianhua QianDepartment of Gynecology and Obstetrics, The First Affiliated Hospital, Zhejiang University School of Medicine, 79 Qingchun Road, Shangcheng District, Hangzhou City, 310003, Zhejiang Province, People's Republic of ChinaTel +8613858028056Email qianjianhua@zju.edu.cnPurpose: Peptidyl arginine deiminase, type VI (PADI6), a member of the subcortical maternal complex, plays an important role in oocyte growth and the development of fertilized oocytes. Human patients with PADI6 mutations can suffer from multiple reproductive deficiencies including hydatidiform moles and miscarriages. Recent studies have demonstrated that the Hippo signaling pathway plays a central role in the specification of the first cell fates and the maintenance of the human placental trophoblast epithelium. The present study aimed to verify the hypothesis that PADI6 regulates the biological functions of trophoblast cells by targeting YAP1 and to explore the mechanism by which PADI6 accomplishes this in trophoblast cells.Methods: Villi from HMs and human trophoblast cell lines were used to identify the localization of PADI6 and YAP1 by immunohistochemistry and immunocytochemistry. PADI6 overexpression and knockdown were induced in human trophoblast cells. Co-immunoprecipitation was used to explore the interaction between PADI6 and YAP1. Wound healing, Transwell and EdU staining assays were used to detect migration, invasion and proliferation. Flow cytometric analysis was used to analyze the cell cycle and apoptosis. β-Tubulin and F-actin levels were determined by Western blot, quantitative real-time PCR and phalloidin staining.Results: The results showed that PADI6 and YAP1 had the same expression pattern in villi and colocalized in the cytotrophoblast. An interaction between PADI6 and YAP1 was also confirmed in human trophoblast cell lines. We found that PADI6 positively regulated the expression of YAP1. Functionally, overexpression of PADI6 promoted cell cycle progression and enhanced migration, invasion, proliferation and apoptosis, whereas downregulation of PADI6 showed the opposite effects.Conclusion: This study demonstrates that YAP1 is a novel target of PADI6 that serves as an important regulator of trophoblast dysfunction. The crosstalk between the Hippo/YAP1 pathway and the SCMC might be a new topic to explore to uncover the pathological mechanisms of HMs.Keywords: PADI6, yes-associated protein, trophoblast cell, hydatidiform moles